2019
DOI: 10.1212/nxi.0000000000000610
|View full text |Cite
|
Sign up to set email alerts
|

Generation of neuroinflammation in human African trypanosomiasis

Abstract: Human African trypanosomiasis (HAT) is caused by infection due to protozoan parasites of the Trypanosoma genus and is a major fatal disease throughout sub-Saharan Africa. After an early hemolymphatic stage in which the peripheral tissues are infected, the parasites enter the CNS causing a constellation of neurologic features. Although the CNS stage of HAT has been recognized for over a century, the mechanisms generating the neuroinflammatory response are complex and not well understood. Therefore a better unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 57 publications
0
30
0
Order By: Relevance
“…It remains to be clarified whether the PGD2 increase in CSF is merely due to the induced inflammatory response by the host or if it also has a parasitic origin since parasites are found in relatively high densities in the meninges during the late stage of the disease. Despite all advances made over the years about the knowledge of the CNS pathology of HAT, which has been nicely reviewed elsewhere [8][9][10][11][12], processes that are ongoing during the late stage of the disease are at present scarcely understood. Perhaps it occurs as a consequence of the difficulty to access and study affected areas.…”
mentioning
confidence: 99%
“…It remains to be clarified whether the PGD2 increase in CSF is merely due to the induced inflammatory response by the host or if it also has a parasitic origin since parasites are found in relatively high densities in the meninges during the late stage of the disease. Despite all advances made over the years about the knowledge of the CNS pathology of HAT, which has been nicely reviewed elsewhere [8][9][10][11][12], processes that are ongoing during the late stage of the disease are at present scarcely understood. Perhaps it occurs as a consequence of the difficulty to access and study affected areas.…”
mentioning
confidence: 99%
“…Some signs such as the presence of an altered gait, incontinence, a reduced Glasgow Coma Scale, that is, altered state of consciousness, could suggest a neurologic evolution of the disease. 16 However, a small difference in symptom between the two patients exist, the first patient presented impaired consciousness with Glasgow Coma Scale 9/15 and a meningeal syndrome. The second patient had acute mastoiditis.…”
Section: Discussionmentioning
confidence: 99%
“…Parasite phospholipase C, protein kinase, and the parasite cysteine protease brucipain also participate in transmigration of trypanosomes into the CNS [ 101 , 174 ] . Furthermore, it has been shown that T. brucei crosses the VE of cerebral blood vessels of mice through interaction with laminin 8 of the ECs [ 97 ] .…”
Section: Human African Trypanosomiasismentioning
confidence: 99%